2016
DOI: 10.1111/cote.12251
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the interaction energy of benzodifuranone dye molecule rings

Abstract: The aim of this paper was to reveal the relationship between the interaction energy of benzodifuranone dyes and dyeing performance indices such as dyeing temperature and colour fastness. Dimer models of benzene–benzene, benzodifuranone–benzene, and benzodifuranone–benzodifuranone configuration were set up, and geometry optimisation and interaction energy were calculated using a density functional theory ωB97XD, 6‐311G++ (d, p) basis set. The calculation results showed that the benzodifuranone molecule had bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…As for ν ar (CC) (DR 9), the frequency shift might be because of the dispersion of DR 9 during the diffusion process. Meanwhile, during the diffusion process, it is observed that the diffusion of DR 9 through the PET film starts at around 800 s and reaches the equilibrium at almost 6500 s. By comparing the ATR–FTIR spectra collected at 800 and 6500 s in the region of 1680–1550 cm –1 during the diffusion process at 140 °C, it can be seen that ν­(CO) of DR 9 shifts toward higher wavenumbers, while δ­(N–H) of DR 9 shifts toward lower wavenumbers; in other words, the intramolecular hydrogen bonds of DR 9 are weakened after diffusion. ν ar (CC) (DR 9) shifts to lower wavenumbers, which could be because of the π–π interactions between DR 9 and PET. In addition, ν­(CO) (PET) moves slightly toward the higher wavenumber as the diffusion process deepens (Figure b), which may be attributed to the dipole–dipole interaction between CO (DR 9) and CO (PET) .…”
Section: Resultsmentioning
confidence: 97%
“…As for ν ar (CC) (DR 9), the frequency shift might be because of the dispersion of DR 9 during the diffusion process. Meanwhile, during the diffusion process, it is observed that the diffusion of DR 9 through the PET film starts at around 800 s and reaches the equilibrium at almost 6500 s. By comparing the ATR–FTIR spectra collected at 800 and 6500 s in the region of 1680–1550 cm –1 during the diffusion process at 140 °C, it can be seen that ν­(CO) of DR 9 shifts toward higher wavenumbers, while δ­(N–H) of DR 9 shifts toward lower wavenumbers; in other words, the intramolecular hydrogen bonds of DR 9 are weakened after diffusion. ν ar (CC) (DR 9) shifts to lower wavenumbers, which could be because of the π–π interactions between DR 9 and PET. In addition, ν­(CO) (PET) moves slightly toward the higher wavenumber as the diffusion process deepens (Figure b), which may be attributed to the dipole–dipole interaction between CO (DR 9) and CO (PET) .…”
Section: Resultsmentioning
confidence: 97%
“…X-ray diffraction (XRD) was performed on a D2 ADVANCE X-ray diffractometer (Bruker Co., Germany) with monochromatic Cu Kα radiation. All calculations of density functional theory were carried out with Gaussian 09 programs . Optimized ground state geometry of the lowest-energy conformer of 5Acl, BPEI and OTCA was calculated at the B3LYP/6-31G­(d) level.…”
Section: Methodsmentioning
confidence: 99%
“…All calculations of density functional theory were carried out with Gaussian 09 programs. 41 Optimized ground state geometry of the lowest-energy conformer of 5Acl, BPEI and OTCA was calculated at the B3LYP/6-31G(d) level. Density distribution of electron cloud was calculated by DFT/B3LYP method with a 6-31G(d) basis set.…”
Section: Preparation Of Mhps and Rpsmentioning
confidence: 99%
“…Thus, it was hardly used in dyeing fabrics. Fortunately, there are some different ways to improve the photo-stability of the dyes, for example improving the photo-stability of dyes using TiO 2 [19], while computational chemistry could estimate behaviors of dyes under light according to quantum chemistry, which could provide theoretical speculations of photo-chemical/light fastness of the dyes [20,21,22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%